Association Between Lighting Level to Subjective Complaints of Visual Fatigue on Operators in the Auto Welder Section - Edza Aria Wikurendra; Muhammad Shafly Rabbani; Globila Nurika (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Good intensity of light dramatically affects the eyes. If there is less intensity of light. the eye muscles contract as much as possible to see objects or vice versa. If this happens continuously, it will cause damage to the eyes. Based on the preliminary study, it was found that as the auto welder operators have the task to observe the results of the auto welder engine to determine the quality of the welder, this type of work needs accuracy so that the right lighting intensity is required. This study aimed to determine the association between the lighting level and subjective visual fatigue complaints on operators in the auto welder section. Methods: The research method used was quantitative, with a cross- sectional approach and observational method. The samples in this study were 18 respondents from the total sampling technique. The instrument used was the Visual Fatigue Index (VTI) questionnaire. Moreover, the analysis of the study results used the one sample T-test statistical test to determine the association between the dependent and independent variables. Results: The one sample T-test results showed p-value = 0.012 < α = 0.05. This result showed an association between the lighting leveland subjective visual fatigue complaints on operators in the auto welder section. Conclusion: In this research, it was found that the majority of lighting levels that did not meet the standards had an association with subjective complaints of visual fatigue on the operators in the auto welder section.Keywords: auto welder, lighting, visual fatigue